Análisis del servicio turístico que ofrecen los guías de deportes extremos en el cantón Baños - Quiñonez Banguera, Raizha Hillary (2021)
Ecuador has many tourist attractions of an incredible unique beauty, attracting national and foreign tourists to our country. The tourist guide represents a primordial role in the orientation of a site, since he/she is responsible for attending the tourist, besides divulging with precision all the informative data of the attraction, the good attention attracts the tourists which makes them want to return. This research study refers to the analysis of the tourist service of the extreme sports guides in the canton of Baños, through this research we seek to support and guide the tour guides to have a training by the collaboration of the authorities of Baños and thus find a tourism development in the sector, This is one of the cantons with a good reception of tourists, also a large part of the guides are not specialized since they are called empirical guides, causing that by not having adequate training they do not acquire the correct and necessary knowledge to offer an excellent service to the tourist. To develop the research we used a bibliographic-documentary methodology based on the collection of information to know the satisfaction of tourists who visit Baños. With the present degree work, the conclusion is that it is important to orient and support the extreme sport guides because, if there is an improvement in their practical, technical and theoretical knowledge, they will offer a good service. To train the extreme sports guides with the support of the GAD of Baños providing knowledge in good tourist service, use of equipment and first aid, in addition to improving the tourism development of the residents of the canton of Baños.